Novel Function of lncRNA ADAMTS9-AS2 in Promoting Temozolomide Resistance in Glioblastoma via Upregulating the FUS/MDM2 Ubiquitination Axis - Yan, Yuanliang; Xu, Zhijie; Chen, Xi; Wang, Xiang; Zeng, Shuangshuang; Zhao, Zijin; Qian, Long; Li, Zhi; Wei, Jie; Huo, Lei; Li, Xuejun; Gong, Zhicheng; et al. (Frontiers in Cell and Developmental Biology, 2019)
Background: LncRNAs have been shown to play essential roles in cancer therapeutic response. However, the detailed mechanism of lncRNAs in temozolomide (TMZ) resistance in glioblastoma (GBM) remain to be elucidated. Methods: To elucidate the mechanism maintaining TMZ resistance, we constructed two TMZ-resistant GBM cell lines (T98G-R/U118-R). LncRNAs from four public datasets were reanalyzed, and the candidate lncRNA ADAMTS9-AS2 was evaluated in TMZ-treated GBM patients and in vitro cell lines. Results: Reanalysis of lncRNA expression profiles identified ADAMTS9-AS2 as significantly overexpressed in TMZ-resistant GBM cells and as positively associated with the IC50 of TMZ in GBM cells. Overexpression of ADAMTS9-AS2 was also significantly associated with poor TMZ response and shorter progression-free survival (PFS) in TMZ-treated GBM patients. Knockdown of ADAMTS9-AS2 inhibited proliferation and attenuated the IC50 of TMZ, as well as mitigating invasion and migration in TMZ-resistant GBM cells. Subsequent investigations indicated that reduced expression of ADAMTS9-AS2 significantly suppressed expression of the FUS protein, which was predicted as a direct substrate of ADAMTS9-AS2. Expression trends of FUS were directly correlated with those of ADAMTS9-AS2, as shown by increasing concentrations and prolonged treatment with TMZ. RNA pull-down and RIP assays indicated that both endogenous and exogenous ADAMTS9-AS2 directly binds to the RRM and Znf_RanBP2 domains of FUS, consequently increasing FUS protein expression. Knockdown of ADAMTS9-AS2 reduced the half-life of FUS and decreased FUS protein stability via K48 ubiquitin degradation. Moreover, the E3 ubiquitin-protein ligase MDM2 interacts with and down regulates FUS, while the RRM and Znf_RanBP2 domains of FUS facilitate its binding with MDM2. ADAMTS9-AS2 decreased the interaction between MDM2 and FUS, which mediates FUS K48 ubiquitination. Additionally, knockdown of the ADAMTS9-AS2/FUS signaling axis significantly alleviated progression and metastasis in TMZ-resistant cells. Conclusion: ADAMTS9-AS2 possessed a novel function that promotes TMZ resistance via upregulating the FUS/MDM2 axis in GBM cells. The RRM or Znf_RanBP2 domains of FUS facilitate the combination of ADAMTS9-AS2 and FUS, competitively inhibiting MDM2-dependent FUS K48 ubiquitination and resulting in enhanced FUS stability and TMZ resistance. Our results suggest that the ADAMTS9-AS2/ FUS/MDM2 axis may represent a suitable prognostic biomarker and a potential target in TMZ-resistant GBM therapy.